The Ethical Limits of Trust in Business Relations - Husted, Bryan W. (Business ethics quarterly, 1998)
This article defines and analyzes the nature of a trust relation. It specifically examines the internal and external morality of trust relations and the ethical limits of those relations. It examines both the ends pursued by trust relations as well as the means by which trust is developed. It shows that the ends need to be evaluated by traditional ethical theories, while the ethical constraints of the trust process depend upon the specific bases of trust. In addition, the consequences of the trust process differ in their impact on the trustor and third parties. Despite the popularity of trust in the literature, this study recommends caution in the use of trust as an ethical basis for economic organization. The optimal form of trust, although still subject to limitations, is fairness-based trust.